ECOCRITICS IN SONG LYRICS COLLECTION BY BARASUARA AND ITS IMPLICATION TOWARDS THE INDONESIAN LANGUAGE LEARNING MATERIAL IN SENIOR HIGH SCHOOL (KUMPULAN LIRIK LAGU BARASUARA BAND KARYA IGA DADA YUDHISTIRA MASSARDI DAN IMPLIKASI DENGAN MATERI PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH MENENGAH ATAS KAJIAN EKOKRTIK SASTRA) - Agus Sulaeman; Koh Young Hun; Aldo Ferdianda (Jurnal Gramatika, 2021)
This study discusses analysis  in Barasuara Band by   Iga Dada Yudhistira Massardi  song lyrics collection and its implications for learning Indonesian in senior high school. From the analysis, there are several songs in the lyrics containing literary ecocritical values, regarding environmental and natural damage due to human actions. The purpose of this study is to describe the literary ecocritical value contained in the collection of Barasuara's song lyrics, in the form of ecocritical values about pollution, natural disasters, housing, and the earth, and its implications for learning Indonesian in senior high school. The approach used is a qualitative approach using content analysis methods while the data collection technique uses documentation study or literature review, in this case the study of the Barasuara Band Song Lyrics Collection is the main data source in research. The data used in this study are the findings of quotations in a collection of song lyrics by  Iga Dada Yudhistira Massardi : 1) Guna Manusia, 2) Tentukan Arah, 3) Barat, 4) Haluan, 5) Tarintih, 6) Pikiran dan Perjalanan, and 7) Mengunci Ingatan which contains a literary ecocritical value. Data collection techniques using documentation study or literature review. Barasuara song lyrics is the main data source in the research. The results of the study found that twenty-six literary ecocritical values contained in the song lyrics collection by the Barasuara band included the values of pollution, dwelling, apocalypse, and the earth. From these findings, this collection of songs can be applied and can be used as teaching material in Indonesian language learning in senior high school class X semester 2 with learning material for poetry musicalization  KD 3. 16       and 4. 16.